Penggunaan Aplikasi Akuntansi untuk Meningkatkan Kinerja Pelaporan Keuangan - Istutik Istutik; Maretha Auliarahma Sugiarto; Widanarni Pudjiastuti (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Technological developments in the digital era have increased. This is a challenge for all business sectors. The emergence of information systems for preparing company financial reports is one of the technological advances. To manage company financial reporting, many cloud-based accounting software and information systems have emerged. Ngalup Collaborative Network manages its financial reporting using Jurnal.Id which provides a number of features to help record accounting and prepare business financial reports more effectively and on time. Jurnal.Id is easy to access at any time using the internet network without needing to be installed on the user's computer or laptop. This research analyzes the effectiveness and efficiency of implementing online accounting software in the operational activities of the Ngalup Collaborative Network in improving financial reporting performance. In its application, Jurnal.Id has been able to assist the accounting section of the Ngalup Collaborative Network in carrying out accounting recording work and preparing financial reports accurately and on time for stakeholder needs.